2021
DOI: 10.3233/thc-218040
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hypertensive disorders in pregnancy using multiple methods: Models with the placental growth factor parameter

Abstract: BACKGROUND: Placental growth factor (PlGF), one of the biomarkers, has a certain predictive effect on hypertensive disorders in pregnancy (HDP). OBJECTIVE: To study the HDP prediction effect of different methods for variable selection and modeling for models containing PlGF. METHODS: For the model containing PlGF, the appropriate range of PlGF parameters needed to be selected. Step-logistic regression and lasso were used to compare the model effect of twice range selection. The PlGF model with good predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…According to clinical needs and model effect, the best HDP prediction model with PlGF parameters in the second trimester (15-26 weeks) was finally selected. However, their performance needs to be improved [ 8 ].…”
Section: Related Workmentioning
confidence: 99%
“…According to clinical needs and model effect, the best HDP prediction model with PlGF parameters in the second trimester (15-26 weeks) was finally selected. However, their performance needs to be improved [ 8 ].…”
Section: Related Workmentioning
confidence: 99%
“…Poon et al ( 29 ) found that the early-onset preeclampsia prediction model had a high detection rate of 93.1% for early-onset preeclampsia, but only 35.7% and 18.3% for late-onset preeclampsia and gestational hypertension. Sun et al ( 30 ) compared the prediction effects of different methods on HDP and found that the Lasso regression method had the best prediction effect.…”
Section: Introductionmentioning
confidence: 99%